INTRAVITREAL ANTI–VASCULAR ENDOTHELIAL GROWTH FACTOR FOR THE MANAGEMENT OF NEOVASCULARIZATION IN RETINOBLASTOMA AFTER INTRAVENOUS AND/OR INTRAARTERIAL CHEMOTHERAPY: Long-Term Outcomes in a Series of 35 Eyes. Issue 12 (December 2019) - Stathopoulos, Christina; Gaillard, Marie-Claire; Moulin, Alexandre; Puccinelli, Francesco; Beck-Popovic, Maja; Munier, Francis L.
Abstract : Purpose: To report the use of anti–vascular endothelial growth factor in the management of retinoblastoma. Methods: Retrospective review of 35 eyes (33 patients) treated with at least one intravitreal anti–vascular endothelial growth factor (ranibizumab and/or aflibercept) for new iris (n = 26) and/or retinal neovascularization (n = 21) after intravenous chemotherapy and/or intraarterial chemotherapy. Results: Most eyes (n = 31/35, 89%) were Group D or E. Previous treatments were salvage intraarterial chemotherapy after intravenous chemotherapy (n = 21/35, 60%), first-line intraarterial chemotherapy (n = 7/35, 20%), and first-line intravenous chemotherapy (n = 7/35, 20%). Associated clinical features were retinal ischemia (94%), retinal detachment (51%), active tumor (34%), intravitreal hemorrhage (43%), and/or glaucoma (17%). Mean 1.6 anti–vascular endothelial growth factor injections/eye were given; 28 eyes received ranibizumab, 2 aflibercept, and 5 both agents. Eight eyes underwent complementary treatments of ischemic retina. Resolution of neovascularization was observed in 28 eyes (n = 28/35, 80%). Globe salvage was achieved in 51% (n = 18/35), including 25% of those with active tumor (n = 3/12). One eye became phthisic. Sixteen eyes were enucleated, nine for tumor relapse/progression. Five eyes had high-risk histopathologic risk factors and received adjuvant intravenous chemotherapy. All patients are alive with no extraocular extension nor metastases (mean follow-up 3.7 years, range 1.1–7.6). Conclusion: Intravitreal anti–vascular endothelial growth factor contributed to a globe salvage rate of 51% by providing conditions to continue conservative treatment. Abstract : Neovascularization as complication of conservative retinoblastoma treatment has been until now only poorly studied and usually treated with enucleation. We report our results of its management with intravitreal anti–vascular endothelial growth factor combined or not with other treatments in eyes with both active and inactive tumor.